Specific game-based performance in elite male adolescent team handball players - Wagner, H.; Hinz, M.; Fuchs, P.; Bell, J. W.; von Duvillard, S. P. (International Journal of Sports Physiology and Performance, 2022)
Purpose: In elite team handball, talent identification and selection of the best young players is a fundamental process in several national federations and clubs; however, literature addressing the specific game-based performance in team handball is almost nonexistent. Consequently, the aim of the study was to assess and compare the team-handball-specific game-based performance of elite male team handball players of different ages. Methods: Twelve under-23, 10 under-19, 10 under-17, and 10 under-15 elite male players performed the team-handball game-based performance test. During testing, oxygen uptake, heart rate, sprinting time in defense, offense, fast breaks, and fast retreats, as well as ball velocity and jump height in the jump shot, were measured. Results: Significant differences (P < .05) between under-23, under-19, under-17, and under-15 players were found for absolute peak oxygen uptake, defense, offense and fast break time, ball velocity, and jump height in the game-based performance test, as well as in body weight and height. Conclusion: The results revealed that with increasing age, elite male team handball players are heavier and taller (body weight and height); faster (team-handball offense, defense, and fast break); jump higher and throw faster (in the team-handball jump shot); and perform better aerobically (absolute peak oxygen uptake). The better performance in the under-23 and under-19 players compared with male adult players competing in a lower National Federation league (not on top-elite level) demonstrates that highly specific game-based physical performance determines the potential for developing young male team handball players for competition at the top level.